2D Material-based Quantum Logic Gate Operating Via Self-Organization of Quantum Dots (Global Journal of Science Frontier Research, 2020)
In the paper, nanotrigger-based electronic device, capable of performing the quantum computation procedure, is described. The device represents a quantum logic gate formed from a two-dimensional material and controlled by a quantum dot. The operation of the quantum dot is analyzed. In the model representation, the transition between two states of the quantum dot, each of which controls the flow of the nanotransistor current (one of the shoulders of the nanotrigger), is equivalent to tunneling through an energy barrier separating the states. Fundamentally important is the fact that in one of these states the quantum dot is diamagnetic, and in the other it is paramagnetic. The paramagnetism of the quantum dot is due to the electronic exchange interaction, characteristic of the systems with unpaired electrons. Thus, the elementary self-organized 2D-material-derived logic gate disclosed in the present work can be employed for design of an electronic reversible unit. In other words, such a unit is able to prepare and to trigger the computation procedure.
Keywords: logic gate; self-organized quantum dot; nanotrigger; quantum computer; graphene